Evaluation of a Swarm Intelligence Approach for Assessing Civil Infrastructure Condition - Thakker, Hemal; Singh, Daljeet Pal; K. N., Raja Praveen; Gupta, Tannmay; Pareek, Ravi Kant (International Journal of Intelligent Systems and Applications in Engineering, 2024)
It is crucial to evaluate the state of civil infrastructure to maintain the durability of these essential systems and ensure public safety. Physical assessments, which are time-consuming, laborious, and prone to human error, are frequently used in traditional methods for evaluating infrastructure status. This study introduces a new Swarm-Intelligent Aquila Optimisation (SIAO) method for assessing the state of civil infrastructure to get beyond these restrictions. The SIAO approach intelligently examines and evaluates the present condition of buildings by examining many characteristics, including structural health, by simulating a swarm's well-organized motion and decisions. Concrete image datasets are gathered to explore the proposed SIAO approach's performance in monitoring the structures' status. The outcomes showed that the SIAO technique performs better than conventional methods in effectiveness, accuracy, and dependability. This strategy could revolutionize the building engineering discipline and support the proactive control and upkeep of vital infrastructure facilities..